Homework Help

# y = 3x^2-x Find the derivative using first principles.

Salutatorian

• Up
• 1
• Down

y = 3x^2-x

Find the derivative using first principles.

Posted by saj-94 on August 28, 2013 at 5:57 PM via web and tagged with math

College Teacher

(Level 1) Educator Emeritus

• Up
• 1
• Down

`y=3x^2-x`

`y=3x^2-x` ------------(1)

For `deltax` small change in x if the change in y is ` deltay ` is then;

`y+deltay=3(x+deltax)^2-(x+deltax)` ---------------(2)

(2)-(1)

`deltay=3(x^2+2x*deltax+deltax ^2)-(x+deltax)-(3x^2-x)`

`deltay =6x*deltax-deltax-3deltax ^2`

Since `deltax` is very small `deltax^2=0`

`deltay =6x*deltax-deltax = deltax(6x-1)`

`(dy)/dx = lim_(deltaxrarr0) (deltay)/(deltax)`

`(dy)/dx = lim_(deltaxrarr0)(deltax(6x-1))/(deltax)`

`(dy)/dx =6x^-1`

So the derivative of y=3x^2-x by first principles is 6x-1.

Posted by jeew-m on August 28, 2013 at 6:06 PM (Answer #1)

College Teacher

(Level 2) Distinguished Educator

• Up
• 1
• Down

The derivative of a function f(x) from first principles is:

`f'(x) = lim_(h->0) (f(x + h) - f(x))/h`

For f(x) = 3x^2 - x

`f'(x) = lim_(h->0) (3(x + h)^2 - (x + h) - (3x^2 - x))/h`

= `lim_(h->0) (3x^2 + 6xh + 3h^2 - x - h - 3x^2 + x)/h`

= `lim_(h->0) (6xh + 3h^2 - h)/h`

= `lim_(h->0) (6x + 3h - 1)`

Substituting h = 0

=> 6x - 1

The derivative of f(x) = 3x^2 - x is f'(x) = 6x - 1

Posted by justaguide on August 28, 2013 at 6:14 PM (Answer #2)